A novel concrete-filled auxetic tube composite structure: Design and compressive characteristic study. (1st October 2022) - Luo, Chen; Ren, Xin; Han, Dong; Zhang, Xue Gang; Zhong, Ru; Zhang, Xiang Yu; Xie, Yi Min
Highlights: A novel concrete-filled auxetic stainless steel tube (CFASST) composite structure was proposed. The proposed CFASST composite structures could provide a desirable radial confinement effect. Decreasing Poisson's ratio could improve the compressive performance of the CFASST composite structure. Abstract: Concrete-filled stainless steel tube (CFSST) members take advantage of the high strength and the outstanding corrosion resistance to act as an important role in civil engineering structures. However, the steel tube could not provide the perfect confinement effect for the core concrete during the initial elastic compression stage because Poisson's ratio of the concrete is smaller than that of the stainless steel tube (SST). In this paper, a novel concrete-filled auxetic stainless steel tube (CFASST) composite structure was designed and manufactured to actively restrain the concrete, making the best use of the desirable deformation characteristics of auxetic tubular structures. The axial compressive performance of these CFASST members and their control factors were investigated experimentally and numerically. Test results were discussed in detail which included failure modes, load versus displacement curves and strain analysis. Finally, parametric analyses were conducted to further study the effects of different parameters (Poisson's ratio, thickness of the stainless tube) on the CFSST composite structure under axial compression. It was found that CFASST composite structures possess an unusual deformation mode and an improved confinement effect.